A Screen for Selective Killing of Cells with Chromosomal Instability Induced by a Spindle Checkpoint Defect - Shaukat, Zeeshan; Wong, Heidi W. S.; Nicolson, Shannon; Saint, Robert B.; Gregory, Stephen L. (PLOS ONE, 2012)
Background The spindle assembly checkpoint is crucial for the maintenance of a stable chromosome number. Defects in the checkpoint lead to Chromosomal INstability (CIN), which is linked to the progression of tumors with poor clinical outcomes such as drug resistance and metastasis. As CIN is not found in normal cells, it offers a cancer-specific target for therapy, which may be particularly valuable because CIN is common in advanced tumours that are resistant to conventional therapy. Principal Findings Here we identify genes that are required for the viability of cells with a CIN phenotype. We have used RNAi knockdown of the spindle assembly checkpoint to induce CIN in Drosophila and then screened the set of kinase and phosphatase genes by RNAi knockdown to identify those that induce apoptosis only in the CIN cells. Genes identified include those involved in JNK signaling pathways and mitotic cytoskeletal regulation. Conclusions/Significance The screen demonstrates that it is feasible to selectively kill cells with CIN induced by spindle checkpoint defects. It has identified candidates that are currently being pursued as cancer therapy targets (e.g. Nek2: NIMA related kinase 2), confirming that the screen is able to identify promising drug targets of clinical significance. In addition, several other candidates were identified that have no previous connection with mitosis or apoptosis. Further screening and detailed characterization of the candidates could potentially lead to the therapies that specifically target advanced cancers that exhibit CIN.